The effect of corporate governance on Islamic banking performance: a maqasid Shari’ah index approach on Indonesian Islamic banks - Rahman, Audia Syafa’atur; Haron, Razali (IIUM Institute of Islamic Banking and Finance (IIiBF), International Islamic University Malaysia (IIUM), 2019)
This study aims to provide empirical evidence on the Maqasid al-Shari’ah performance of Islamic banks in Indonesia for the period from 2012 to 2016. The Simple Additive Weighting (TSAW) is employed to obtain the performance of IBs according to the Maqasid al-Shari’ah. This study found that the Maqasid Index for Indonesia IBs within the range between 11% and 28% with only few banks achieved above 20%. The impact of SSB characteristics and board structures are then tested on the IBs Maqasid al-Shari’ah performance. Regression result indicates that SSB characteristics (SSB size, SSB cross membership, SSB Education and SSB reputation) and board structures (Board size and Board independence) have an essential role in improving the performance of IBs. The findings denote SSB with smaller size, higher portion of SSB cross membership, lesser SSB hold doctorate degree, lesser reputable scholar, more members on board of directors, and less independence non-executive directors enhance the performance of IBs. This study offers practical implication and regulators in Indonesia should set up and impose a more robust and new tool to evaluate the Maqasid al-Shari’ah performance index in order to assess how far the role of IBs have contributed to the society. This will help all stakeholders to have informed decision which not only concentrates on performance based on financial ratios but also the entire dimensions of IBs that reflect the main purpose of IBs.